An overview of the current evidences on the role of iron in colorectal cancer: a review - Yousefi, Mohammad Hasan; Masoudi, Alireza; Saberi Rounkian, Masoumeh; Mansouri, Maryam; Hojat, Bita; Kaveh Samani, Marzieh; Veisi, Razieh; Honarvar Bakeshloo, Parisa; Nosratipour, Reza; Afkhami, Hamed; Saeb, Sepideh (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is a common and lethal malignancy that affects millions of people worldwide. Iron is an essential micronutrient that plays a vital role in various biological processes, but also has pro-oxidant and pro-inflammatory effects that may contribute to carcinogenesis. The relationship between iron and CRC is complex and influenced by multiple factors, such as dietary intake, absorption, storage, metabolism, and excretion of iron, as well as genetic and environmental factors that modulate iron homeostasis. This review article aims to provide an overview of the current evidences on the role of iron in CRC, discussing the potential mechanisms by which iron may affect CRC development and progression, as well as the implications for prevention and treatment. This review tries to focus on the following aspects: an introduction to iron and its role in CRC, role of heme and non-heme iron in CRC, dietary patterns, nutrition, and CRC, iron overload in CRC, iron deficiency and its role in CRC especially in surgery outcome and iron therapy and blood transfusion in CRC.